2008
DOI: 10.2215/cjn.02040408
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Renal and Metabolic Effects Associated with Oral Sodium Phosphate Bowel Preparation

Abstract: Colorectal cancer can be prevented by the removal of adenomatous polyps during screening colonoscopy, but adequate bowel preparation is required. Oral sodium phosphate (OSP), an effective bowel purgative, is available over the counter and requires a substantially lower volume than polyethylene glycol-based preparative agents. Accumulating reports implicate OSP in electrolyte disturbances as well as acute kidney injury (AKI) in a syndrome termed phosphate nephropathy (a form of nephrocalcinosis). Despite publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 87 publications
(47 reference statements)
1
64
0
5
Order By: Relevance
“…The excess absorbed phosphate is then filtrated through the glomeruli, passed through the tubules, and is excreted into the urine, except when the concentration of phosphate in the primary urine exceeds its solubility, in which case calcium phosphate crystals are formed. These crystals form CPDs on tubular epithelial cells, leading to luminal obstruction (8) and also causing an immune reaction, tubular inflammation, and damage to the tubulointerstitial area (9). Previous studies of APhN reported diffuse, abundant CPDs obstructing the tubular lumens, thus supporting this hypothesis (Table 4).…”
Section: Discussionmentioning
confidence: 62%
“…The excess absorbed phosphate is then filtrated through the glomeruli, passed through the tubules, and is excreted into the urine, except when the concentration of phosphate in the primary urine exceeds its solubility, in which case calcium phosphate crystals are formed. These crystals form CPDs on tubular epithelial cells, leading to luminal obstruction (8) and also causing an immune reaction, tubular inflammation, and damage to the tubulointerstitial area (9). Previous studies of APhN reported diffuse, abundant CPDs obstructing the tubular lumens, thus supporting this hypothesis (Table 4).…”
Section: Discussionmentioning
confidence: 62%
“…As NaP preparations have a low volume and are better tolerated, they are preferred more by clinicians. However, NaP solutions may cause severe fluid-electrolyte shifts and acute phosphate nephropathy (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopists currently pay more attention to patients' comfort; for example, polyethylene glycol is being replaced by sodium phosphate for bowel preparation before colonoscopy [17] . However, recent reports have shown that phosphate nephropathy may complicate bowel preparation using sodium phosphate, even after a single preparation [18] . Another example is the use of propofol for sedation in replacement of benzodiazepines [19] .…”
Section: Discussionmentioning
confidence: 99%